Controversy as Marketing Strategy: Indonesian Celebrities Promoting Skincare through Public Image Polarization - Elfina Okto Posmaida Damanik; Mahaitin H Sinaga; Jusra Tampubolon; Hengki Mangiring Parulian Simarmata (Manajemen: Jurnal Ekonomi, 2025)
This study aims to determine the impact of controversial figures in marketing strategies in the skincare industry. The research focuses on three public figures: Nikita Mirzani, Dr. Richard Lee, and “Dokter Detektif." This study uses a qualitative study approach to explore the polarization of public image and the role of celebrities in influencing consumer perceptions, brand trust, and purchase intent. Data was collected through social media content analysis, online media documentation, and a literature review of previous studies. The findings reveal three core themes: (1) controversial personal branding attracts engagement and emotional resonance, (2) buzz marketing tactics trigger virality through peripheral cues rather than rational persuasion, and (3) consumer ambivalence emerges between entertainment value and brand credibility. However, the use of controversy also poses long-term reputational risks for the associated brands. Although this study is limited to qualitative methods, it offers theoretical insights and practical recommendations for ethically managing influencer campaigns in culturally sensitive digital markets.